2019
DOI: 10.22159/ijap.2019v11i2.31308
|View full text |Cite
|
Sign up to set email alerts
|

Hibiscus Leaf Mucilage as Stabiliser for Pharmaceutical Disperse Systems

Dipanjana Ash,
Priyanka Ghosh,
Sutapa Biswas Masjee
et al.

Abstract: Objective: Stable pharmaceutical disperse systems are defined as heterogeneous, biphasic systems as suspensions and emulsions, stabilized by third agent or stabilizer. The aim of the present investigation was to extract mucilage from the leaves of Hibiscus rosa-sinesnsis L. and explore its ability to function as stabiliser for adult (10%w/v) and paediatric (2.4%w/v) paracetamol (PCM) suspensions and 2% v/v sunflower oil emulsions. Methods: Isolated mucilage powder was subjected to phytochemical tests to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The physicochemical properties of HM polymer were characterized by XRD, FTIR, UV-Vis, SEM, DLS, BET, and Swelling ratio. A very low amount of crystallinity structures is present in hibiscus mucilage extract, as suggested by the existing literature (Ash et al 2019, Sen et al 2022 while the XRD result indicated HM polymer did not show any crystallinity in structure and it carried only an amorphous pattern. Additionally, FTIR confirms the characteristic vibrational and thereby suggesting its purity.…”
Section: Discussionmentioning
confidence: 64%
“…The physicochemical properties of HM polymer were characterized by XRD, FTIR, UV-Vis, SEM, DLS, BET, and Swelling ratio. A very low amount of crystallinity structures is present in hibiscus mucilage extract, as suggested by the existing literature (Ash et al 2019, Sen et al 2022 while the XRD result indicated HM polymer did not show any crystallinity in structure and it carried only an amorphous pattern. Additionally, FTIR confirms the characteristic vibrational and thereby suggesting its purity.…”
Section: Discussionmentioning
confidence: 64%